The impact of a recreational program using mini-games to improve some mental abilities (attention and sensory cognition) in children with motor hyperactivity - GUERGOUR, Mohamed; ABDERRAHMANE, Mourad; REBOUH, Salah (International Journal of Psychosocial Rehabilitation, 2022)
This study aims to recognize the importance of the proposed recreational program using mini games to improve some mental abilities (Attention and sensory perception) In pupils with excessive motor hyperactivity in the primary phase and highlighting the various difficulties they suffer that adversely affect their educational achievement, although the level of attention and sensory perception above average, motor hyperactivity affects this. and the two researchers used the experimental curriculum using the experimental design of one group, namely the experimental sample with tribal and post-metric measurement and using the following statistical methods: arithmetic average, standard deviation, test "T" StewdentIn this study, we found that the recreational program using mini games has a positive impact on improving some mental abilities (attention and sensory perception) and also contributed to improving their educational achievement.